The Role of Mass Spectrometry in Structural Studies of Flavin-Based Electron Bifurcating Enzymes - Tokmina-Lukaszewska, Monika; Patterson, Angela; Berry, Luke; Scott, Liam; Balasubramanian, Narayanaganesh; Bothner, Brian (Frontiers in Microbiology, 2018)
For decades biologists and biochemists have taken advantage of atomic resolution structural models of proteins from X-ray crystallography, nuclear magnetic resonance spectroscopy, and more recently cryo-electron microscopy. However, not all proteins relent to structural analyses using these approaches, and as the depth of knowledge increases, additional data elucidating a mechanistic understanding of protein function is desired. Flavin-based electron bifurcating enzymes, which are responsible for producing high energy compounds through the simultaneous endergonic and exergonic reduction of two intercellular electron carriers (i.e. NAD+ and ferredoxin) are one class of proteins that have challenged structural biologists and in which there is great interest to understand the mechanism behind electron gating. A limited number of X-ray crystallography projects have been successful, however, it is clear that to understand how these enzymes function techniques that can reveal detailed in solution information about protein structure, dynamics, and interactions involved in the bifurcating reaction is needed. In this review, we cover a general set of mass spectrometry-based techniques that, combined with protein modeling, are capable of providing information on both protein structure and dynamics. Techniques discussed include surface labeling, covalent cross-linking, native mass spectrometry and hydrogen/deuterium exchange. We cover how biophysical data can be used to validate computationally generated protein models and develop mechanistic explanations for regulation and performance of enzymes and protein complexes. Our focus will be on flavin-based electron bifurcating enzymes, but the broad applicability of the techniques will be showcased.